Low-temperature synthesis of carbon nanotubes on indium tin oxide electrodes for organic solar cells - Capasso, Andrea; Salamandra, Luigi; Di Carlo, Aldo; Bell, John Marcus; Motta, Nunzio (Beilstein Journal of Nanotechnology, 2012)
The electrical performance of indium tin oxide (ITO) coated glass was improved by including a controlled layer of carbon nanotubes directly on top of the ITO film. Multiwall carbon nanotubes (MWCNTs) were synthesized by chemical vapor deposition, using ultrathin Fe layers as catalyst. The process parameters (temperature, gas flow and duration) were carefully refined to obtain the appropriate size and density of MWCNTs with a minimum decrease of the light harvesting in the cell. When used as anodes for organic solar cells based on poly(3-hexylthiophene) (P3HT) and phenyl-C61-butyric acid methyl ester (PCBM), the MWCNT-enhanced electrodes are found to improve the charge-carrier extraction from the photoactive blend, thanks to the additional percolation paths provided by the CNTs. The work function of as-modified ITO surfaces was measured by the Kelvin probe method to be 4.95 eV, resulting in an improved matching to the highest occupied molecular orbital level of the P3HT. This is in turn expected to increase the hole transport and collection at the anode, contributing to the significant increase of current density and open-circuit voltage observed in test cells created with such MWCNT-enhanced electrodes.
Keywords: carbon nanotubes; electrode; indium tin oxide; Kelvin probe; organic photovoltaics